Formulation of Dragon Fruit Skin Nail Polish Cosmetic Preparations (Hylocereus Polyrhizus) - Dinasti; Sri Yolandari; Sitti Alfyanita Ilham (Journal of Health Science and Pharmacy, 2025)
Background: Dragon fruit (Hylocereus polyrhizus) is widely recognized for its nutritional value and health benefits. However, its peel is often discarded as waste, despite containing high levels of anthocyanins. These natural pigments are responsible for the red coloration of dragon fruit and have considerable potential as safe, environmentally friendly alternatives to synthetic dyes, particularly in cosmetic applications. Objectives: This study aims to evaluate the feasibility of utilizing dragon fruit peel extract as a natural dye in nail polish formulations and to assess the physical characteristics of the resulting cosmetic products. Methods: An experimental laboratory-based study was conducted by formulating nail polish using dragon fruit peel extract at three different concentrations: 8% (F1), 9% (F2), and 10% (F3). The formulated products were evaluated through organoleptic testing to assess physical appearance attributes, including color, form, and aroma. Panelist preferences were recorded to determine the most acceptable formulation. Results: The findings demonstrate that dragon fruit peel extract can be successfully used as a natural coloring agent in nail polish formulations. Among the three formulations, F3 (10% extract concentration) was identified as the most preferred, with 8 out of 10 panelists selecting it as the best formulation. This formulation exhibited the most attractive color intensity and the most favorable physical characteristics. Conclusion: Dragon fruit peel extract shows strong potential as a natural dye in cosmetic products, particularly nail polish. The use of a 10% extract concentration produced the most acceptable formulation, supporting the utilization of agricultural waste as a sustainable and safe alternative to synthetic cosmetic dyes.